Brexit and Anti-Parliament Discourses among Conservative MPs (2016–2019). Issue 2 (30th November 2020) - Alexandre-Collier, Agnès
Abstract: Brexit seems to have produced a new form of narrative in the Conservative Party in which some Conservative MPs brand themselves first and foremost as representatives of 'the people'. Following on from the 2016 EU referendum, a new discourse has become prominent in the party and has also been developed as a new critique of the British Parliament. An analysis of Hansard debates between July 2016 and December 2019 helps identify different forms of anti-Parliament narrative which denounce the paralysis of the legislative process as well as its anti-democratic and conspiratorial features. By doing so, they reveal a radical departure from the historic values of the Conservative party such as the 'veneration' of Parliament but question the claim that this may signal the surge of a new type of populism.